Decision Making in the Context of Improving the Performance of Educational Staff at Santa Lucia Sei Rotan Elementary School - Esther Justina Sinaga; Saloma Banjarnahor; Yasaratodo Wau; Benyamin Situmorang; Rosmala Dewi (Budapest International Research and Critics University, 2023)
Decision making in order to improve the performance of educational staff and compare it with practices that occur in the field, to make decisions both operational decisions and strategic decisions that have an impact on the future of education units, especially students, educators and education staff. This research method uses qualitative. This type of research is descriptive qualitative research. The results show that decision-making in order to improve the performance of educational staff carried out by the principal of the Santa Lusia Sei Rotan Elementary School has been going well so far, this can be seen from the process and stages carried out by the principal of the decision-making school, namely the observation stage, collecting data, planning and identifying problems related to education in schools, then conducting deliberations among teachers, to adopt a policy, carrying out interpersonal approaches to teachers to carry out organizing activities, providing ideas and brilliant ideas, involving teachers in training activities and competitions. The strategy carried out by an education unit leader or school principal requires a decision-making process in order to improve the performance of educational staff, namely identifying a problem, clarifying and prioritizing goals, creating choices, assessing choices, comparing predicted consequences. on each choice with goals, choose the option with consequences with goals.